2009
DOI: 10.1071/rd08176
|View full text |Cite
|
Sign up to set email alerts
|

Multipotential ability of primitive germ cells from neonatal pig testis cultured in vitro

Abstract: Gonocytes are progenitor-type germ cells that arise from primordial germ cells and differentiate further into spermatogonia, thereby initiating spermatogenesis. In the present study, freshly isolated gonocytes were found to have either weak or no expression of pluripotency determining transcription factors, such as POU5F1, SOX2 and C-MYC. Interestingly, the expression of these transcription factors, as well as other vital transcription factors, such as NANOG, KLF4 and DAZL, were markedly upregulated in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Previous studies demonstrated that several pluripotent/multipotent germline stem cells have been established and characterized by different research groups using various protocols, and murine and human male GSCs can be cultured for long periods and retain the capacity to differentiate into multiple cell types in the presence of serum or feeder cells in vitro. Recently, porcine, goat and bovine mGSCs were cultured and characterized, and these cells shared similar characteristics of ES cells and GSCs (Kanatsu-Shinohara et al 2008;Goel et al 2009;Kuijk et al 2009;Hua et al 2011;Zeng et al 2013;Zheng et al 2013;Park et al 2014). However, the methods available for isolating SSCs and mGSCs from porcine testicular cells have a low efficiency of cell separating, and it is difficult to establish a stable livestock mGSCs line Zheng et al 2013;Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that several pluripotent/multipotent germline stem cells have been established and characterized by different research groups using various protocols, and murine and human male GSCs can be cultured for long periods and retain the capacity to differentiate into multiple cell types in the presence of serum or feeder cells in vitro. Recently, porcine, goat and bovine mGSCs were cultured and characterized, and these cells shared similar characteristics of ES cells and GSCs (Kanatsu-Shinohara et al 2008;Goel et al 2009;Kuijk et al 2009;Hua et al 2011;Zeng et al 2013;Zheng et al 2013;Park et al 2014). However, the methods available for isolating SSCs and mGSCs from porcine testicular cells have a low efficiency of cell separating, and it is difficult to establish a stable livestock mGSCs line Zheng et al 2013;Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, propagation of porcine mGSCs could be maintained in the presence of 1% FBS and supplementation of growth factors for one month (Zheng et al 2013). The authors evaluated the effects of growth factors based on the number of colonies of SSC-like, and expression level of SSC markers and suggest that FGF can impede successful derivation of porcine SSCs from neonate pig testis (Goel et al 2009). Update, the effects of cytokines and growth factors on porcine mGSCs were not clear (Goel et al 2009;Zheng et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of these genes may be required for the survival and proliferation of gonocytes. In the pig, upregulation of pluripotency-related genes in gonocytes in primary culture was shown to stimulate the proliferation and stem cell potential of the gonocytes (Goel et al 2009), suggesting that DBA-coated plates can support the proliferation and survival of cultured bovine germ cells. Meanwhile, the expression of NANOG on the DBA-precoated plates was decreased, whereas UCHL1 expression increased.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, the expression of vital pluripotency-related genes, such as NANOG and POU5F1, is essential, but their expression gradually decreases as the passage number increases (Goel et al 2009). The pluripotent state in cultured germ cells can be supported by using ECM components that interact with adhesion molecules on the cell surface (Chai and Leong 2007), which suggests that some cell surface molecules can regulate the expression of genes associated with a pluripotent state in cultured germ cells.…”
Section: Introductionmentioning
confidence: 99%